2017
DOI: 10.1200/jop.2017.020883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Palliative Care on Aggressiveness of End-of-Life Care Among Patients With Advanced Cancer

Abstract: This population-based study found that palliative care substantially decreased health-care use among Medicare beneficiaries with advanced cancer. Given the increasing number of elderly patients with advanced cancer, this study emphasizes the importance of early integration of palliative care alongside standard oncologic care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 29 publications
4
55
2
Order By: Relevance
“…Those aggressive EOL treatments raised EOL-care costs, regardless of the healthcare system examined, without any significant benefit for the patient or his/her family in terms of improved quality of life 89. Early access to palliative care lowered the number of patients given aggressive treatments 90. Unfortunately, in most healthcare systems, early access to palliative care during the course of these cancers remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Those aggressive EOL treatments raised EOL-care costs, regardless of the healthcare system examined, without any significant benefit for the patient or his/her family in terms of improved quality of life 89. Early access to palliative care lowered the number of patients given aggressive treatments 90. Unfortunately, in most healthcare systems, early access to palliative care during the course of these cancers remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…71 In contrast, in the USA a similar population-based study examining use of palliative care services in Medicare patients with advanced cancer reported that only 4.5% of patients had had a palliative care encounter. 72…”
Section: End-of-life Carementioning
confidence: 99%
“…In a recent review Dalal and Bruera have reported that the magnitude of hospital cost savings with PC involvement ranged from 9% to 32% and these savings were higher when a PC team was involved earlier (within two days from the patient’s admission) [ 50 ]. Two recent studies [ 62 , 63 ] have pointed out that cancer patients’ care was characterized by high-cost and low-value interventions, high hospital readmission rates, prolonged length of stay, hospital deaths, and frequent use of chemotherapy and other disease-centered interventions near the EoL. These data are indicative of poor care coordination and inadequate EoL planning, and such a management translates into cost escalation, while patients continue to receive non-beneficial and burdensome health interventions at the EoL.…”
Section: What Is the Impact Of In-hospital Palliative Care Servicementioning
confidence: 99%